A New Culture of Learning: Digital Storytelling and Faith Formation. (March 2014) - Hess, Mary E.
Abstract How has the "new culture of learning" begun to transform us, and in what ways might the faith formation practices of religious communities be impacted by the shift? Recent research funded by the MacArthur Foundation lays an empirical basis for recognizing shifts in learning brought about by widespread access to digital technologies. The implications of that research, in turn, pose widespread challenges to the work of faith formation in contemporary communities of faith. Communicative theologies may be best poised to engage these challenges through the practices of digital storytelling.